Emergency Management for Disasters in Malaysian Hotel Industry - AlBattat, Ahmad Rasmi; Mat Som, Ahmad Puad; Abukhalifeh, Ala`a (EDP Sciences, 2014)
This paper aims to identify major emergencies that have the potential to place Malaysian hotels in emergency and disaster situations; investigate how hotels were prepared for emergencies, how they manage and overcome emergencies when occurred; and limitations and factors influencing successful emergency planning and adoption emergency management in Malaysian hotels. Face-to-face interview with managers from three, four and five star hotels from different backgrounds: local; regional; and International in Kuala Lumpur, Subang, and Putrajaya are undertaken. The result revealed that Malaysian hotels are exposed to a wide range of natural and man-made disasters. Malaysian hotels lack proactive emergency planning and a lot of constraints which impede successful emergency planning for disasters in the hotel industry in Malaysia, with emphasizing on the relevant authority’s role to demonstrate emergency management to hotels convincing them to adopt such practices, so they can be able to cope with emergencies effectively.